2001
DOI: 10.1002/zoo.1033
|View full text |Cite
|
Sign up to set email alerts
|

Managing the socialization of an adult male gorilla (Gorilla gorilla gorilla) with a history of social deprivation

Abstract: Most non-human primates exhibit aggression during changes in social group composition. In zoological parks, group membership changes are necessary for optimal population management, but can elicit problematic aggression. Furthermore, some primates with a long history of social deprivation are hyperaggressive when introduced to conspecifics. In this study of one male gorilla with a 30-year history of social deprivation, we assessed the rate of aggression quantitatively during a four-step socialization procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Given the contribution of agonistic behavior categories (including active and passive aggression) to general behavior patterns, the results suggest that the sequential method of introduction did effectively manage aggression during these introductions. These findings closely match those described by Burks et al [2001], and suggest that the general patterns observed are likely to be found in other applications of the sequential introduction method.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given the contribution of agonistic behavior categories (including active and passive aggression) to general behavior patterns, the results suggest that the sequential method of introduction did effectively manage aggression during these introductions. These findings closely match those described by Burks et al [2001], and suggest that the general patterns observed are likely to be found in other applications of the sequential introduction method.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, a modified version of the methodology described by Burks et al [2001] appeared appropriate for use in investigating two approaches to introductions in this species. One method involved decision-making based primarily on intuitive assessments by animal managers, while the other method rigorously and systematically followed the introduction steps as outlined in the protocol.…”
Section: Social Organization Of African Elephantsmentioning
confidence: 99%
“…Past observations of intra-specific introductions have shown that at each stage, aggression among individuals will generally increase at first but then return to a pre-introduction baseline [Burks et al, 1998[Burks et al, , 2001. Thus, we expected to observe this pattern of aggression here, although it had not been previously documented in an interspecific introduction.…”
Section: Introductionmentioning
confidence: 67%
“…Captive facilities sometimes find it necessary to add or remove an animal from the social group (Burks et al, 2001). These animal movements are similar to a fission-fusion society in the wild, albeit involuntary in captivity.…”
Section: Introductionmentioning
confidence: 98%
“…The death or removal of a close associate, change in the dominance hierarchy, or the introduction of a new individual are all likely to affect the social behavior of small groups more so than larger groups. Additionally, changes in social behavior may be more pronounced in captivity than in the wild (Burks et al, 2001). In a study of pigtail monkeys (Macaca nemestrina, Erwin & Erwin, 1976), an increase in group size resulted in an increased frequency of aggressive behaviors.…”
Section: Introductionmentioning
confidence: 99%